Physical Modeling of Oil Displacement in the Multifunctional Surfactant-based Chemical Composition. (August 2020) - Kozlov, V V; Altunina, L K; Chernova, U V; Sholidodov, M R
Abstract: The paper presents the test results of a new multifunctional chemical composition based on surfactants in the process of displacement of heavy high-viscosity oil. Physical modeling of the oil displacement process was carried out in a laboratory setup which allows modeling heterogeneity of the oil-saturated formation. As a result of experiments it was found that the use of a multifunctional chemical oil-displacing composition based on a surfactant leads not only to a change in the filtration flows within the heterogeneous reservoir model but also to an increase in the oil displacement coefficient.